2022
DOI: 10.1016/j.surg.2021.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Short-term perioperative outcomes among patients with concurrent asymptomatic and mild SARS-CoV-2 infection: A retrospective, multicenter study

Abstract: Background Previous studies report high rates of postoperative morbidity and mortality among SARS-CoV-2 (COVID-19) patients. With routine preoperative screening, we are identifying an increasing number of patients with asymptomatic and mild COVID-19. Based on these prior studies, we hypothesized that patients with asymptomatic and mild COVID-19 infections have low perioperative morbidity and mortality. The purpose of this study was to determine the risk of perioperative morbidity and mortality ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Inclusion of any patient with a positive test result, regardless of timing, makes these results more applicable to the late stage of the pandemic, when most COVID-19 infections have occurred outside of the 7- to 10-day infection window used in most initial perioperative studies. 30 , 31 The requirement for a positive PCR test result allowed for a clear diagnosis as well as time frame; however, patients without a positive PCR test result who did have COVID-19 could have been missed. In addition, the use of a large database and robust informatics infrastructure with rigorous sensitivity analyses allowed for more continuous assessment of risk, rather than arbitrary cutoffs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusion of any patient with a positive test result, regardless of timing, makes these results more applicable to the late stage of the pandemic, when most COVID-19 infections have occurred outside of the 7- to 10-day infection window used in most initial perioperative studies. 30 , 31 The requirement for a positive PCR test result allowed for a clear diagnosis as well as time frame; however, patients without a positive PCR test result who did have COVID-19 could have been missed. In addition, the use of a large database and robust informatics infrastructure with rigorous sensitivity analyses allowed for more continuous assessment of risk, rather than arbitrary cutoffs.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a composite outcome is a unique method to measure risk associated with COVID-19, which is critical when deciding perioperative recommendations. Inclusion of any patient with a positive test result, regardless of timing, makes these results more applicable to the late stage of the pandemic, when most COVID-19 infections have occurred outside of the 7- to 10-day infection window used in most initial perioperative studies . The requirement for a positive PCR test result allowed for a clear diagnosis as well as time frame; however, patients without a positive PCR test result who did have COVID-19 could have been missed.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Jonker et al, 7 nearly a quarter of patients undergoing elective or emergent surgery during or after recovering from COVID-19 infection encountered a pulmonary complication. Even in asymptomatic or mild COVID-19 infection, Weitzner et al 15 found that 11% of patients had a pulmonary complication in the first 30 days postoperatively. A recent study by Deng et al 8 found an increased risk of pneumonia in patients undergoing major elective surgery 0 to 4 weeks and 4 to 8 weeks after diagnosis of COVID-19, although the overall rate of pneumonia was lower than that reported in other studies at 7% and 3%, respectively.This study also identified a higher risk of pneumonia in joint arthroplasty surgery, LF, UE surgery, and FA surgery; the increased risk of pneumonia in the UE group may be attributed or partially attributed to a higher rate of COPD and emphysema in the patients with preoperative COVID-19 that remained after propensity-score matching.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that patients with asymptomatic infection or with only mild symptoms show a lower risk of perioperative morbidity and mortality associated with operations. Therefore, the surgical risk assessment for such patients should be reconsidered from that for patients with symptomatic infection[ 59 ]. However, there are no cohort studies to prove the effect of asymptomatic infection on surgical or prognostic recovery of hip fracture.…”
Section: Perspectivementioning
confidence: 99%